Anti-static sole material and preparation method thereof

By introducing graphene and polypyrrole into the PVC and EVA matrix of anti-static sole materials and connecting quaternary ammonium salts to the surface of functional fillers, the problems of poor anti-static durability and affected mechanical properties of existing materials are solved, and excellent results are achieved antistatic properties and good mechanical properties.

CN119391102APending Publication Date: 2025-02-07文江
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411508804.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The antistatic durability of existing antistatic sole materials is poor, and the amount of polymer antistatic agent added greatly affects the mechanical properties of the material.

Method used

Using PVC and EVA as substrates, polypyrrole is introduced on the graphene surface to form a conductive path, and a positively charged quaternary ammonium salt is connected to the functional filler surface to form an electrostatic leakage path.

Benefits of technology

It achieves that the sole material maintains excellent antistatic properties after use without affecting the mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005104834630000091
    Figure BDA0005104834630000091
Patent Text Reader

Abstract

The invention discloses an anti-static sole material and a preparation method thereof, and belongs to the technical field of high polymer materials, the anti-static sole material comprises the following raw materials by weight: 60-75 parts of PVC, 5-10 parts of EVA, 1-1.2 parts of a stabilizer, 10-16 parts of a plasticizer, 10-15 parts of a functional filler, and 2-3 parts of a foaming agent; the functional filler is introduced, the base material is endowed with excellent antistatic performance while the mechanical property of the sole material is ensured, the quaternary ammonium salt with positive charges is connected to the surface of the functional filler, when negative charges are generated, the charges can be adsorbed on the positive part of a lipophilic group of the quaternary ammonium salt, and the negative part of a hydrophilic group is directionally exposed in air, so that the antistatic performance of the sole material is improved. The antistatic sole material prepared by the preparation method disclosed by the invention can absorb water molecules to form an electrostatic leakage path, so that the sole material prepared by the preparation method has excellent conductive performance and still keeps excellent antistatic performance when generating friction with a road surface after being used.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to an antistatic sole material and a preparation method thereof. Background Art

[0002] When people walk, the friction between the soles of shoes and the ground is likely to generate static electricity, and in the petrochemical industry, static electricity is likely to generate sparks and cause explosions. Therefore, when operating in the petrochemical industry, operators need to wear anti-static shoes to eliminate the hidden dangers of static electricity. Anti-static shoes can conduct static electricity from the human body to the ground, thereby eliminating human static electricity, and at the same time effectively suppress the dust generated by people walking in the clean room; anti-static shoes generally use PU or PVC materials that dissipate electricity to make the soles.

[0003] Ordinary PVC or PU materials have a high surface resistivity (10 10 -10 15 Ω) and low dielectric constant, it is easy to generate static electricity. In order to achieve the anti-static effect, people generally add antistatic agents. Traditional antistatic agents are generally composed of surfactants, which have good antistatic properties, but poor antistatic durability; non-ionic antistatic agents mainly rely on migrating to the surface of the material to absorb moisture in the air to produce electrolyte membranes to conduct electricity, which are highly dependent on temperature and humidity, and their durability is limited; polymer antistatic agents require a high addition amount to achieve an effective antistatic effect, which has a greater impact on the overall mechanical properties of the material. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides an antistatic sole material and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] An antistatic sole material comprises the following raw materials in parts by weight: 60-75 parts of PVC, 5-10 parts of EVA, 1-1.2 parts of stabilizer, 10-16 parts of plasticizer, 10-15 parts of functional filler, and 2-3 parts of foaming agent;

[0007] The functional filler is prepared by the following steps:

[0008] Step S1, pouring graphene and hexadecyltrimethylammonium bromide into distilled water, ultrasonically stirring for 15 minutes, dropping concentrated hydrochloric acid, placing in an ice water bath and continuing to stir for 15 minutes, then adding pyrrole, stirring at a uniform speed and reacting for 15 minutes, adding a 10% ammonium persulfate aqueous solution by mass fraction, continuing to stir and react for 24 hours, filtering after the reaction, washing with anhydrous ethanol and deionized water three times respectively, freeze-drying to obtain a functional matrix, and controlling the amount ratio of graphene, hexadecyltrimethylammonium bromide, concentrated hydrochloric acid, pyrrole, ammonium persulfate aqueous solution and deionized water to be 0.1-0.2g:0.4-0.6g:1-1.5mL:0.2-0.3mL:20mL:100mL;

[0009] In step S1, long-chain hexadecyltrimethylammonium bromide is adsorbed on the graphene surface, and ammonium persulfate is added as an oxidant. Pyrrole itself is electrically neutral, and loses an electron after being oxidized to form positively charged cationic radicals, which then combine into pairs, disproportionate, and repeatedly polymerize to form polypyrrole. By introducing polypyrrole on the graphene surface, on the one hand, the compatibility of graphene and the matrix can be improved, and on the other hand, polypyrrole itself has conductivity, which can cooperate with graphene to form a conductive path and improve the antistatic performance of the matrix.

[0010] Step S2, adding lauric acid and 2-bromoethanol into a three-necked flask, placing the flask in a 65°C oil bath for heat preservation and reacting for 10 minutes, adding concentrated sulfuric acid dropwise after the reaction, reflux reacting for 3-5 hours, cooling to room temperature after the reaction, washing with deionized water until the washing liquid is neutral, recrystallizing, filtering, and drying to obtain an intermediate, wherein the amount ratio of lauric acid, 2-bromoethanol and concentrated sulfuric acid is controlled to be 2-3g:1.2-1.5g:0.1-0.2mL;

[0011] In step S2, concentrated sulfuric acid is used as a catalyst to cause esterification reaction between lauric acid and 2-bromoethanol to synthesize an intermediate;

[0012] Step S3, adding the intermediate and the functional matrix to N, N-dimethylformamide, heating and reflux for reaction for 6 hours, and after the reaction, removing the solvent by rotary evaporation, vacuum drying for 4 hours to obtain a functional filler, and controlling the dosage ratio of the intermediate, the functional matrix and N, N-dimethylformamide to be 0.3-0.5g: 0.1-0.15g: 50mL.

[0013] In step S3, the pyridine structure on the functional matrix can undergo a quaternization reaction with the bromine element on the intermediate, thereby introducing a quaternary ammonium salt structure. When the PVC material is used as a sole material and rubs against the ground, a negative charge will be generated. Therefore, the present invention connects a quaternary ammonium salt with a positive charge to the surface of the functional filler. When a negative charge is generated, the charge will be adsorbed on the positively charged part of the lipophilic group of the quaternary ammonium salt, and the negatively charged part of the hydrophilic group will be directionally exposed to the air, absorbing water molecules, and forming a path for static electricity leakage.

[0014] Furthermore, the stabilizer is barium stearate, the plasticizer is epoxidized soybean oil, and the foaming agent is AC foaming agent.

[0015] A method for preparing an antistatic sole material comprises the following steps:

[0016] The first step is to add PVC, EVA, stabilizer, functional filler and plasticizer into a mixer, mix them evenly at 90-95°C, add a foaming agent and mix evenly to obtain a mixture;

[0017] In the second step, the obtained mixture is added into a twin-screw extruder, extruded and granulated at 130-135° C., then dried at 100-110° C. for 10 hours, and finally transferred into an injection molding machine for injection molding at 150-160° C. to obtain an antistatic sole material.

[0018] Beneficial effects of the present invention:

[0019] The invention prepares an antistatic sole material, which uses PVC and EVA as a matrix and introduces a functional filler. The mechanical properties of the sole material are ensured while the matrix material is endowed with excellent antistatic properties. In the preparation process, the functional filler firstly adsorbs long-chain hexadecyltrimethylammonium bromide on the surface of graphene, adds ammonium persulfate as an oxidant, and repeatedly polymerizes pyrrole to form polypyrrole. By introducing polypyrrole on the surface of graphene, on the one hand, the compatibility of graphene and the matrix can be improved, and on the other hand, polypyrrole itself has conductivity and can cooperate with graphene to form a conductive path, thereby improving the antistatic property of the matrix. Then, concentrated sulfuric acid is used as a catalyst, lauric acid and 2 - bromoethanol undergoes an esterification reaction to synthesize an intermediate, and finally the pyridine structure undergoes a quaternization reaction with the bromine element on the intermediate, thereby introducing a quaternary ammonium salt structure. When the PVC material is used as a sole material and rubs against the ground, a negative charge will be generated. Therefore, the present invention connects a quaternary ammonium salt with a positive charge to the surface of the functional filler. When a negative charge is generated, the charge will be adsorbed on the positively charged part of the lipophilic group of the quaternary ammonium salt, and the negatively charged part of the hydrophilic group will be directionally exposed to the air, absorbing water molecules to form a path for static electricity leakage. Therefore, the sole material prepared by the present invention itself has excellent conductive properties. At the same time, it will still maintain excellent antistatic properties when it rubs against the road surface after use. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Example 1

[0022] An antistatic sole material, comprising the following raw materials in parts by weight: 60 parts of PVC, 5 parts of EVA, 1 part of stabilizer, 10 parts of plasticizer, 10 parts of functional filler, and 2 parts of foaming agent;

[0023] The antistatic sole material is made by the following steps:

[0024] The first step is to add PVC, EVA, stabilizer, functional filler and plasticizer into a mixer, mix them evenly at 90°C, add a foaming agent and mix them evenly to obtain a mixture;

[0025] In the second step, the prepared mixture is added into a twin-screw extruder, extruded and granulated at 130°C, and then dried at 100°C for 10 hours, and finally transferred into an injection molding machine for injection molding at 150°C to obtain an antistatic sole material.

[0026] The functional filler is prepared by the following steps:

[0027] Step S1, pouring graphene and hexadecyltrimethylammonium bromide into distilled water, ultrasonically stirring for 15 minutes, dropping concentrated hydrochloric acid, placing in an ice water bath and continuing to stir for 15 minutes, then adding pyrrole, stirring and reacting at a uniform speed for 15 minutes, adding a 10% mass fraction ammonium persulfate aqueous solution, continuing to stir and react for 24 hours, filtering after the reaction, washing with anhydrous ethanol and deionized water three times respectively, freeze-drying to obtain a functional matrix, and controlling the amount ratio of graphene, hexadecyltrimethylammonium bromide, concentrated hydrochloric acid, pyrrole, ammonium persulfate aqueous solution and deionized water to be 0.1g:0.4g:1mL:0.2mL:20mL:100mL;

[0028] Step S2, adding lauric acid and 2-bromoethanol into a three-necked flask, placing it in a 65°C oil bath for insulation and reacting for 10 minutes, adding concentrated sulfuric acid dropwise after the reaction, reflux reacting for 3-5 hours, cooling to room temperature after the reaction, washing with deionized water until the washing liquid is neutral, recrystallizing, filtering, and drying to obtain an intermediate, wherein the amount ratio of lauric acid, 2-bromoethanol and concentrated sulfuric acid is controlled to be 2g:1.2g:0.1mL;

[0029] Step S3, adding the intermediate and the functional matrix to N,N-dimethylformamide, heating and reflux for 6 hours, and after the reaction, removing the solvent by rotary evaporation, vacuum drying for 4 hours to obtain the functional filler, and controlling the dosage ratio of the intermediate, the functional matrix and N,N-dimethylformamide to be 0.3g:0.1g:50mL.

[0030] The stabilizer is barium stearate, the plasticizer is epoxidized soybean oil, and the foaming agent is AC foaming agent.

[0031] Example 2

[0032] An antistatic sole material comprises the following raw materials in parts by weight: 65 parts of PVC, 6 parts of EVA, 1.1 parts of stabilizer, 12 parts of plasticizer, 12 parts of functional filler, and 2.2 parts of foaming agent;

[0033] The antistatic sole material is made by the following steps:

[0034] The first step is to add PVC, EVA, stabilizer, functional filler and plasticizer into a mixer, mix them evenly at 90°C, add a foaming agent and mix them evenly to obtain a mixture;

[0035] In the second step, the prepared mixture is added into a twin-screw extruder, extruded and granulated at 130°C, then dried at 105°C for 10 hours, and finally transferred into an injection molding machine for injection molding at 150°C to obtain an antistatic sole material.

[0036] The functional filler is prepared by the following steps:

[0037] Step S1, pouring graphene and hexadecyltrimethylammonium bromide into distilled water, ultrasonically stirring for 15 minutes, dropping concentrated hydrochloric acid, placing in an ice water bath and continuing to stir for 15 minutes, then adding pyrrole, stirring and reacting at a uniform speed for 15 minutes, adding a 10% ammonium persulfate aqueous solution by mass fraction, continuing to stir and react for 24 hours, filtering after the reaction, washing with anhydrous ethanol and deionized water three times respectively, freeze-drying to obtain a functional matrix, and controlling the amount ratio of graphene, hexadecyltrimethylammonium bromide, concentrated hydrochloric acid, pyrrole, ammonium persulfate aqueous solution and deionized water to be 0.14g:0.5g:1.2mL:0.2mL:20mL:100mL;

[0038] Step S2, adding lauric acid and 2-bromoethanol into a three-necked flask, placing it in a 65°C oil bath for insulation and reacting for 10 minutes, adding concentrated sulfuric acid dropwise after the reaction, reflux reacting for 4 hours, cooling to room temperature after the reaction, washing with deionized water until the washing liquid is neutral, recrystallizing, filtering, and drying to obtain an intermediate, wherein the amount ratio of lauric acid, 2-bromoethanol and concentrated sulfuric acid is controlled to be 2.5g:1.4g:0.1mL;

[0039] Step S3, adding the intermediate and the functional matrix to N,N-dimethylformamide, heating and reflux for 6 hours, and after the reaction, removing the solvent by rotary evaporation, vacuum drying for 4 hours to obtain a functional filler, and controlling the dosage ratio of the intermediate, the functional matrix and N,N-dimethylformamide to be 0.4g:0.12g:50mL.

[0040] The stabilizer is barium stearate, the plasticizer is epoxidized soybean oil, and the foaming agent is AC foaming agent.

[0041] Example 3

[0042] An antistatic sole material comprises the following raw materials in parts by weight: 70 parts of PVC, 8 parts of EVA, 1.2 parts of stabilizer, 14 parts of plasticizer, 14 parts of functional filler, and 3 parts of foaming agent;

[0043] The antistatic sole material is made by the following steps:

[0044] The first step is to add PVC, EVA, stabilizer, functional filler and plasticizer into a mixer, mix them evenly at 95°C, add a foaming agent and mix them evenly to obtain a mixture;

[0045] In the second step, the prepared mixture is added into a twin-screw extruder, extruded and granulated at 135°C, and then dried at 105°C for 10 hours, and finally transferred into an injection molding machine for injection molding at 160°C to obtain an antistatic sole material.

[0046] The functional filler is prepared by the following steps:

[0047] Step S1, pouring graphene and hexadecyltrimethylammonium bromide into distilled water, ultrasonically stirring for 15 minutes, dropping concentrated hydrochloric acid, placing in an ice water bath and continuing to stir for 15 minutes, then adding pyrrole, stirring and reacting at a uniform speed for 15 minutes, adding a 10% mass fraction ammonium persulfate aqueous solution, continuing to stir and react for 24 hours, filtering after the reaction, washing with anhydrous ethanol and deionized water three times respectively, freeze-drying to obtain a functional matrix, and controlling the amount ratio of graphene, hexadecyltrimethylammonium bromide, concentrated hydrochloric acid, pyrrole, ammonium persulfate aqueous solution and deionized water to be 0.18g:0.6g:1.4mL:0.3mL:20mL:100mL;

[0048] Step S2, adding lauric acid and 2-bromoethanol into a three-necked flask, placing the flask in a 65°C oil bath for heat preservation and reacting for 10 minutes, adding concentrated sulfuric acid dropwise after the reaction, reflux reacting for 5 hours, cooling to room temperature after the reaction, washing with deionized water until the washing liquid is neutral, recrystallizing, filtering, and drying to obtain an intermediate, wherein the amount ratio of lauric acid, 2-bromoethanol and concentrated sulfuric acid is controlled to be 3g:1.4g:0.2mL;

[0049] Step S3, adding the intermediate and the functional matrix to N,N-dimethylformamide, heating and reflux for 6 hours, and after the reaction, removing the solvent by rotary evaporation, vacuum drying for 4 hours to obtain a functional filler, and controlling the dosage ratio of the intermediate, the functional matrix and N,N-dimethylformamide to be 0.5g:0.14g:50mL.

[0050] The stabilizer is barium stearate, the plasticizer is epoxidized soybean oil, and the foaming agent is AC foaming agent.

[0051] Example 4

[0052] An antistatic sole material comprises the following raw materials in parts by weight: 75 parts of PVC, 10 parts of EVA, 1.2 parts of stabilizer, 16 parts of plasticizer, 15 parts of functional filler, and 3 parts of foaming agent;

[0053] The antistatic sole material is made by the following steps:

[0054] The first step is to add PVC, EVA, stabilizer, functional filler and plasticizer into a mixer, mix them evenly at 95°C, add a foaming agent and mix them evenly to obtain a mixture;

[0055] In the second step, the prepared mixture is added into a twin-screw extruder, extruded and granulated at 135°C, and then dried at 110°C for 10 hours, and finally transferred into an injection molding machine for injection molding at 160°C to obtain an antistatic sole material.

[0056] The functional filler is prepared by the following steps:

[0057] Step S1, pouring graphene and hexadecyltrimethylammonium bromide into distilled water, ultrasonically stirring for 15 minutes, dropping concentrated hydrochloric acid, placing in an ice water bath and continuing to stir for 15 minutes, then adding pyrrole, stirring and reacting at a uniform speed for 15 minutes, adding a 10% ammonium persulfate aqueous solution by mass fraction, continuing to stir and react for 24 hours, filtering after the reaction, washing with anhydrous ethanol and deionized water three times respectively, freeze-drying to obtain a functional matrix, and controlling the amount ratio of graphene, hexadecyltrimethylammonium bromide, concentrated hydrochloric acid, pyrrole, ammonium persulfate aqueous solution and deionized water to be 0.2g:0.6g:1.5mL:0.3mL:20mL:100mL;

[0058] Step S2, adding lauric acid and 2-bromoethanol into a three-necked flask, placing the flask in a 65°C oil bath for heat preservation and reacting for 10 minutes, adding concentrated sulfuric acid dropwise after the reaction, reflux reacting for 5 hours, cooling to room temperature after the reaction, washing with deionized water until the washing liquid is neutral, recrystallizing, filtering, and drying to obtain an intermediate, wherein the amount ratio of lauric acid, 2-bromoethanol and concentrated sulfuric acid is controlled to be 3g:1.5g:0.2mL;

[0059] Step S3, adding the intermediate and the functional matrix to N,N-dimethylformamide, heating and reflux for 6 hours, and after the reaction, removing the solvent by rotary evaporation, vacuum drying for 4 hours to obtain a functional filler, and controlling the dosage ratio of the intermediate, the functional matrix and N,N-dimethylformamide to be 0.5g:0.15g:50mL.

[0060] The stabilizer is barium stearate, the plasticizer is epoxidized soybean oil, and the foaming agent is AC foaming agent.

[0061] Comparative Example 1

[0062] Compared with Example 1, this comparative example uses graphene as the functional filler.

[0063] Comparative Example 2

[0064] This comparative example is an antistatic shoe sole material produced by a certain company on the market.

[0065] The performance of the sole materials prepared in Examples 1-4 and Comparative Examples 1-2 was tested, and the results are shown in Table 1 below:

[0066] Table 1

[0067] Antistatic performance: Refer to GB / T 1410-2006 to test the surface resistivity of each sole material. The smaller the surface resistivity, the better the antistatic performance.

[0068] Impact strength: Refer to GB / T1043.1-2008 to test the impact strength of each sole material. The higher the impact strength, the better the toughness.

[0069] Table 1

[0070]

[0071] It can be seen from Table 1 above that the sole materials prepared in Examples 1 to 4 of the present invention have excellent antistatic properties and good mechanical properties.

[0072] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. An antistatic sole material, characterized in that: The raw materials include the following parts by weight: 60-75 parts of PVC, 5-10 parts of EVA, 1-1.2 parts of stabilizer, 10-16 parts of plasticizer, 10-15 parts of functional filler, and 2-3 parts of foaming agent; The functional filler is prepared by the following steps: Step S1, pouring graphene and hexadecyltrimethylammonium bromide into distilled water, ultrasonically stirring for 15 minutes, adding concentrated hydrochloric acid dropwise, placing in an ice water bath and continuing to stir for 15 minutes, then adding pyrrole, stirring at a uniform speed and reacting for 15 minutes, adding a 10% mass fraction of ammonium persulfate aqueous solution, continuing to stir and react for 24 hours, filtering after the reaction, washing with anhydrous ethanol and deionized water three times respectively, and freeze-drying to obtain a functional matrix; Step S2, adding lauric acid and 2-bromoethanol into a three-necked flask, placing it in a 65°C oil bath for heat preservation and reacting for 10 minutes, adding concentrated sulfuric acid dropwise after the reaction, reflux reacting for 3-5 hours, cooling to room temperature after the reaction, washing with deionized water until the washing liquid is neutral, recrystallizing, filtering, and drying to obtain an intermediate; Step S3, adding the intermediate and the functional matrix into N,N-dimethylformamide, heating and refluxing for 6 hours, and after the reaction, removing the solvent by rotary evaporation, and vacuum drying for 4 hours to obtain the functional filler.

2. The antistatic sole material according to claim 1, characterized in that: In step S1, the amount ratio of graphene, hexadecyltrimethylammonium bromide, concentrated hydrochloric acid, pyrrole, aqueous ammonium persulfate solution and deionized water is controlled to be 0.1-0.2 g: 0.4-0.6 g: 1-1.5 mL: 0.2-0.3 mL: 20 mL: 100 mL.

3. The antistatic sole material according to claim 1, characterized in that: In step S2, the dosage ratio of lauric acid, 2-bromoethanol and concentrated sulfuric acid is controlled to be 2-3 g: 1.2-1.5g:0.1-0.2mL.

4. The antistatic sole material according to claim 1, characterized in that: In step S3, the dosage ratio of the intermediate, the functional matrix and N,N-dimethylformamide is controlled to be 0.3-0.5 g: 0.1-0.15 g: 50 mL.

5. The antistatic sole material according to claim 1, characterized in that: The stabilizer is barium stearate, the plasticizer is epoxidized soybean oil, and the foaming agent is AC foaming agent.

6. The method for preparing an antistatic sole material according to claim 1, characterized in that: The steps include: The first step is to add PVC, EVA, stabilizer, functional filler and plasticizer into a mixer, mix them evenly at 90-95°C, add a foaming agent and mix evenly to obtain a mixture; In the second step, the obtained mixture is added into a twin-screw extruder, extruded and granulated at 130-135° C., then dried at 100-110° C. for 10 hours, and finally transferred into an injection molding machine for injection molding at 150-160° C. to obtain an antistatic sole material.